Intra-population Variation in Albizia procera : POD, Seed and Germination Characteristics - Gera, Neelu; Gera, Mohit; Purohit, Mamta; Agarwal, Rashmi (Indian Forester, 2001)
In order to estimate intra-population variability, some mother trees of Albizia procera of Jabalpur (Madhya Pradesh) region were evaluated for their pod, seed and germination characteristics. Significant variation within the population was recorded with respect to almost all morphological characters of pod, seed and germination. Large amount of variation was observed in mother trees dbh, seed weight per pod, percentage of deformed seed, germination per cent, percentage of hard and dead seed and field emergence. No significant relationship between mother tree dbh and any of the parameter studied was observed except for percentage of hard seed. Selection of superior trees based on germination testing in addition to tree characters like dbh has been emphasised for quality seed collection.